Effect of Storage Time Duration on the Quality of Immersion Oirom Kepuh Vegetable Material (Sterculia foetida L) on Imaging of Plant Tissue of Shallot Cell - Mautuka, Zakarias Adrianto; Manimoy, Herianus; Koly, Faryda Veronica Lamma; Karbeka, Martasiana; Botahala, Loth (Jurnal Kimia Fullerene, 2025)
The dependence of optical microscopes on one of the consumables, especially at high magnification, so that the imaging results are clearly visible or not blurry, is immersion oil. In an effort to answer this need, a study has been conducted to find an alternative immersion oil by utilizing vegetable oil from the kepuh plant (Sterculia Foetida L) from Alor Regency. This study tested the quality of kepuh seed meat oil from soxhlet extraction and purified using the Deguming, Neutralization, Bleaching, Stearin, Centrifugation methods, and stored in glass bottles, wrapped in aluminum foil, and stored at room temperature (25-280C) from 2016 to 2024 (8 years). The test used three parameters, namely first; comparison of physical and chemical properties parameters, namely density, viscosity, refractive index, acid number and Aperture Value for kepuh oil data in 2016 and 2024, were recorded to have changed, but the imaging photographs still provided the same brightness as standard oil. Second; the GC-MS identification parameters showed that, even though there were 32 peaks in the kepuh oil spectrum, and the nomination of two compounds was identified, namely linoleic acid 34.58%, stearic acid 6.98%, the imaging effect was still clearly visible. Third, a comparison of the imaging results of standard immersion oil and immersion oil from kepuh for oil conditions in 2024 showed imaging results that were not significantly different.